PENGARUH KEBIASAAN MEMBACA DAN METODE BELAJAR TERHADAP KEMAMPUAN MENULIS RESENSI BUKU - Trikawati; Wulandari, Ratih Ayu; Yuniar, Euis Ismayati; Nurjaman; Budiyanto, Agung (JEDLISH : Journal Of Education and English Language Teaching, 2023)
The purpose of this study was to determine the effect of reading habits on students' ability to write book reviews, the effect of learning methods on students' ability to write book reviews, and the effect of interaction on the ability to write book reviews in class XI SMA Nurul Hasanah Ciheulang in the 2022/2023 academic year. This study used an experimental method and took a sample of 40 people from 100 students at Nurul Hasanah Ciheulang High School in the 2022/2023 academic year who were the objects of research. Data collection was carried out by distributing questionnaires or questionnaires for the Reading Habits variable, treatment or action tests for the Question and Answer Learning Method variable, and a written test in the form of descriptions for the Book Review Writing Ability variable. Data analysis was carried out using SPSS 16. This research was conducted from September to November 2022. The results showed that: 1) there is a significant effect of reading habits on the ability to write book reviews; 2) there is a significant effect of the Learning Method on the ability to write book reviews; 3) there is no effect of the Interaction of Reading Habits and Learning Methods on the Ability to Write Book Reviews. The research hypothesis was tested using a two-way analysis of variance (ANOVA) with the results of F count > F table, namely: X1: F count 48,650 > F table: 4.08, X2: F count 24.976 > F table: 3.09 and X1 X2 F count = 0.599 < F table = 3.09.